Answer:
- center: (2, -6)
- vertices: (2, -4), (2, -8)
Explanation:
Rearranging the equation to standard form helps answer this question.
... -4(x^2 -4x) +(y^2 +12y) = -16 . . . subtract the constant, group x-terms, y-terms
... -4(x^2 -4x +4) +(y^2 +12y +36) = -16 -4(4) +36
... -4(x -2)^2 +(y +6)^2 = 4 . . . . write as squares
... ((y +6)/2)^2 -(x -2)^2 = 1 . . . . divide by 4
Now, this is in the form ...
... ((y -k)/a)^2 -((x -h)/b)^2 = 1
which has center (h, k) and vertices (h, k±a).
This form tells you the center is (x, y) = (2, -6), and the vertices are (2, -4) and (2, -8).